Contemporary social evils / edited by David Utting. - Utting, David (Policy Press, 2009)
Which underlying problems pose the greatest threat to British society in the 21st century? A hundred years after its philanthropist founder identified poverty, alcohol, drugs and gambling among the social evils of his time, the Joseph Rowntree Foundation initiated a major consultation among leading thinkers, activists and commentators, as well as the wider public. The findings have now been brought together in this fascinating book. Individual contributors range across the political spectrum but the book also reports the results from a web survey and consultation with groups whose voices are less often heard. The results suggest that while some evils - like poverty - endure as undisputed causes of social harm, more recent sources of social misery, such as an alleged rise in selfish consumerism and a perceived decline in personal responsibility and family commitment, attract controversy.